High grade dysplasia or esophageal adenocarcinoma in patients with a history of Roux-en-Y gastric bypass surgery: a case series - Alaber, Omer; Mansoor, Emad; Perez, Lady Katherine Mejia; Dumot, John; Bhatt, Amit; Chak, Amitabh (Endoscopy, 2020)
Background Roux-en-Y gastric bypass (RYGB) is the favored bariatric option in patients with gastroesophageal reflux and Barrett’s esophagus because it prevents reflux. Weight loss and decreased reflux following RYGB could theoretically minimize the risk of progression to cancer. We aimed to demonstrate the management of high grade dysplasia (HGD) and esophageal adenocarcinoma (EAC) developing in patients after RYGB.Methods A prospectively maintained database was searched to identify cases of HGD and cancer in RYGB patients. Charts were reviewed for past history, endoscopic findings, endoscopic therapy, and pathology findings.Results There were five cases where HGD/EAC developed several years after RYGB. The prior bariatric surgery precluded curative esophagectomy, illustrating the management challenges. All but one of the patients were uniquely and successfully managed with endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD).Conclusions RYGB patients are still at risk of developing esophageal cancer. Patients at risk should be screened prior to RYGB and those with Barret’s esophagus need to undergo rigorous endoscopic surveillance following surgery. If detected early, EMR and ESD are invaluable in managing those who progress.